Forgotten Prophet. William Henry Hechler and the rise of political Zionism - Maaß, Enzo (Nordisk judaistik/Scandinavian Jewish Studies, 2002)
Reverend William Henry Hechler was of outstanding significance for the mediation of Theodor Herzl’s Zionist ideas to the German and English aristocracy from 1896 to 1904. In spite of this he has for the most part been left overseen, and therefore almost forgotten. Intending to reverse that trend, this article presents a brief biographical sketch of William Hechler, and discusses his relation to Theodor Herzl and the emerging Zionist movement. It highlights their different personalities and the incommensurability of their fundamental ideas. Further, Hechler’s most central publication, The Restoration of the Jews to Palestine (1882), is presented in its historical context and in regard to its posthumous reception. Consequently previous readings of this document are questioned and subsequently dismissed. Instead a new picture of this hitherto almost unknown document will emerge. Finally William Hechler’s prophetical endeavours are briefly outlined, critically reviewed and cautiously re-dated to the midst of the 1890s. Thus, the article promotes an alternative perspective on the spread and success of the young Zionist movement: By focusing on Hechler’s ability to transform Herzl’s political message into a semi-political or religious one, the way is paved for another understanding of the breakthrough and acceptance of Zionism.